Children's Values And The Sustainability Of Education In The Toba Community - Rachman Hakim; Firman; Mohd. Suhadi Bin Mohamed Sidik (Risâlah Jurnal Pendidikan dan Studi Islam, 2025)
The Toba Batak ethnic group has a cultural philosophy to guide their lives. To achieve this philosophy they carry out education because they are aware that education is a step in achieving this philosophy. This research aims to analyze Batak parents' perspectives on education. This research method uses a qualitative method in the form of a literature review. Data collection in this research uses library research as literature material that can present data and is accompanied by supporting documents which are important references in this study. The results of this research show that Batak parents highly value education and will strive for education whatever the circumstances. Because for Batak parents, children are pride, honor, wealth and the most valuable possessions for the family.